Evaluation the Age and Gender Association in Iraqi Patients with High Grade Glioma - Shamsuldeen, Hadeer Hashim; Barraj, Abed Hassan; Hammadi, Sameer Hameed (Iraqi Journal of Science, 2025)
The objective of this study is to investigate the potential association between age, gender, and the incidence of glioma. Thirty-four paraffin embedded tissue samples from patients with high grade glioma, (13female and 21 male), and thirty as control (20 female and 10 male) were randomly selected. All samples with age range (13-70 years) with mean age of 44.94 ± 2.99. Patient samples were collected from the archives of the Neurological Hospital in Baghdad. Tissue sections were stained with haematoxylin and eosin for histopathological examinations conducted from December 2022 to July 2023. The results indicated a significant difference P≤0.05 between Glioma and gender p-value 0.0437) in both sexes, with male patients have a higher incidence according to the percentage (61.76%) with age average (51.62). A highly significant correlation (P≤0.01) was found between glioma and age group, with the highest infection rate (47.06%) observed at the age group 46-65year, it was also noted that females are infected at a younger age with age average younger than (35).